Peran Sektor Kesehatan Dalam Menunjang Kualitas Sumber Daya Manusia Dan Dampaknya Terhadap Pembangunan Ekonomi - Alamsyah Agit; Mashuri Masri; Rusny Rusny (CV. Ulil Albab Corp, 2026)
This study aims to analyze the role of the health sector in supporting the quality of human resources and its impact on economic development in Indonesia. The study used a descriptive quantitative method utilizing data from the Central Statistics Agency (BPS) for the 2021–2025 period and relevant literature. The data analyzed included the health sector budget, health insurance coverage, the number of health workers, the Human Development Index (HDI), and economic growth. The results indicate that the health sector plays a strategic role in human capital formation through improvements in health, labor productivity, and life expectancy. This is reflected in the upward trend in Indonesia's HDI during 2021–2025 and the continued positive trend in economic growth. Theoretically, these findings support human capital theory, the health-led growth hypothesis, and endogenous growth theory, which position health as a key determinant of economic growth. However, the study also found inefficiencies in health budget realization and disparities in health facilities between regions, potentially hampering the optimization of its impact. Therefore, the health sector needs to be positioned as a long-term development investment, not simply a burden on public spending.